Serret-Frenet Formulas for Octonionic Curves - Bektas, Ozcan; Yuce, Salim (SOC PARANAENSE MATEMATICA, 2020)
In this paper, we define spatial octonionic curves (SOC) in R( )(7)and octonionic curves (OC) in R-8 by using octonions. Firstly, we determine Serret-Frenet equations, and curvatures of the SOC in R-7. Then, Serret-Frenet equations for the OC in R-8 are calculated with the help of Serret-Frenet equations of SOC in R-7.
Keywords: Serret-Frenet formulas; Spatial octonionic curve; Octonionic curve; Curvature; Torsion; Mathematics